Biodiversity Disclosure and Firm Value: Evidence from Indonesia - Wulansari, Winda; Arham, Qumil Laila; Marlion, Farid Ahmad; Fajri, Diatul; Gampito, Gampito (MABIS Jurnal Manajemen Bisnis Syariah, 2026)
This study investigates the association between biodiversity disclosure and firm value from the perspectives of stakeholder and signalling theories. The sample consists of manufacturing firms listed on the Indonesian Stock Exchange (IDX) over the 2018–2023 period, comprising 363 firm-year observations. Using a panel regression model with fixed effect estimation, the results reveal a positive association between biodiversity disclosure and firm value. These findings support stakeholder and signalling theories in explaining the role of biodiversity disclosure in enhancing firms' market value. By mitigating information asymmetry, biodiversity disclosure may reduce uncertainty among market participants, thereby contributing to more positive firm valuation. This study offers implications for regulators by highlighting the need to strengthen regulations that promote awareness of biodiversity-related issues and improve transparency in corporate biodiversity performance.